ANALISIS RISIKO KECELAKAAN KERJA MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) PADA PROYEK PEMBANGUNAN JALAN LINTAS SELATAN - Fatma Mirrohmatil Maula; I Nyoman Dita Pahang Putra (Racic : Rab Construction Research, 2025)
The construction sector is considered one of the industries with a high level of occupational accident risk due to complex activities, the use of heavy equipment, and dynamic site conditions. This study aims to assess occupational accident risks in the South Cross Road (Jalan Lintas Selatan/JLS) Lot 2 construction project located in Blitar Regency by applying the Hazard and Operability Study (HAZOP) method. The analysis focuses on four major types of work: blasting, earthworks and embankment, asphalt paving, and erection of girders. Primary data were collected through questionnaires distributed to field experts and analyzed quantitatively by calculating the Severity Index (SI) and Likelihood Index (LI), which were then classified using a Risk Matrix based on the AS/NZS 4360 standard. The results identified 42 validated work-related risks, most of which were associated with the erection girder activities. Prior to implementing risk controls, 18 risks were categorized as high risk. After applying control measures—including engineering controls, administrative procedures, and personal protective equipment (PPE)—14 risks were reduced to low risk. However, 3 risks remained in the high-risk category and require further mitigation. These findings demonstrate that HAZOP is an effective method for identifying and evaluating occupational accident risks in construction projects.